Polythiophene Coated Cellulosic Fibers from Banana Stem for Improved Electrical, Mechanical, Thermal and Dielectric Properties of Polypropylene Composites - Thekkedath, J.; Bipinbal, P. K.; Thomas, T.; Narayanankutty, S. K. (Journal of Scientific Research, 2020)
Incorporating conducting polymer coated fibers in a nonconducting base polymer has proven to be an effective method for the preparation of conducting composites. In the present work, banana fibers, cellulosic microfibers from waste biomass, were used for the coating of conducting polymer through in situ polymerization of thiophene on the fiber surface. The polythiophene (PTH) coated fibers were used as the conducting elements in a general-purpose thermoplastic, polypropylene (PP). The prepared composites were examined for electrical, thermal, mechanical, dynamic mechanical and dielectric properties. Formation of a continuous conducting network of PTH coated fibers in the polymer matrix imparted 6 fold increase in conductivity, 22 % improvement in tensile strength and 47% improvement in tensile modulus. Thermal degradation temperature of polypropylene was improved up to 26 oC. An exceptional improvement of more than 3 orders of magnitude in dielectric constant could be achieved for the composites making them suitable for capacitor applications.